2011
DOI: 10.1212/wnl.0b013e318224afa3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations with brain microbleeds

Abstract: Given the known associations of APOE alleles with lobar intracerebral hemorrhage and cerebral amyloid angiopathy, these findings support the concept that strictly lobar BMBs may be an imaging biomarker of cerebral amyloid angiopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
6
38
4
Order By: Relevance
“…31 The APOE ε4 gene was associated with the presence of strictly lobar CMBs. 31,32 Overall, prevalence of CMBs in our study confirms the age-stratified prevalence of CMBs reported in the Rotterdam Scan Study (mean age of our study population, 66 years; age range, 46-85 years). 31 Prevalence of CMBs was similar in offspring and control subjects, suggesting that the propensity of familial longevity is not associated with a lower susceptibility to CMBs.…”
supporting
confidence: 89%
“…31 The APOE ε4 gene was associated with the presence of strictly lobar CMBs. 31,32 Overall, prevalence of CMBs in our study confirms the age-stratified prevalence of CMBs reported in the Rotterdam Scan Study (mean age of our study population, 66 years; age range, 46-85 years). 31 Prevalence of CMBs was similar in offspring and control subjects, suggesting that the propensity of familial longevity is not associated with a lower susceptibility to CMBs.…”
supporting
confidence: 89%
“…56 In line with our results, they found that APOE e4 carriers had a significantly increased risk of having at least one CMB compared to APOE e33 carriers, 56 with a stronger association for lobar CMB. They did not find a significant relationship between APOE e2 and CMB, regardless of their location.…”
supporting
confidence: 88%
“…In terms of CMB, this report does not align with recent meta‐analyses that concluded significant deleterious effects of APOE ε4 6, 7. Of those meta‐analyses, Schilling et al .…”
Section: Discussioncontrasting
confidence: 85%
“…6 (‘healthy’ n  = 5387; P  = 0·002) and Maxwell et al . 7 (total n  = 7351; P  < 0·01). These two reports also had a degree of overlapping datasets.…”
Section: Introductionmentioning
confidence: 98%